Functional profile determination "trained" and "untrained" by the speed of the bar on the bench press - W. Albarracín; I Bautista; L. J. Chirosa; I. Martín; I. J. Chirosa (Federación Extremeña de Balonmano; University of Extremadura, 2012)
A descriptive study was designed to explore differences in strength, power and velocity in an incremental load protocol in bench press (PB), to obtain an indicator to catalogue a subject as "trained" or "untrained" in the PB exercise.. Thirty male subjects consisted two groups, "trained group", consisted of the participants whose one repetition maximum (1RM) exceeded his body weight (BW) and "untrained group" consisted of participants whose 1RM was less than their BW. The value of 1RM was 82.33 ± 11.09 kg and 59.67 ± 5.16 kg, in the trained and untrained groups, respectively. The indicator of the level of strength (kg 1RM / kg BW) in the trained group was greater than 1, and lower in the untrained group. The average strength showed significant differences (p < 0.05) in the 60, 80% and 1RM. Average power and peak power were higher in the trained group in all analyzed intensities, with the exception of the 1RM. Average velocity and peak velocity showed significant differences between the two groups in the first two intensities analyzed. The main conclusion of this study is provides a functional profile of subjects as "trained", when the 1RM and BW ratio is equal to or greater than 1 (1RM>BW), while when this ratio is less than 1 (1RM<BW), subjects can be categorized as "untrained" in BP. Also this study demonstrates that "trained" subjects with a 20 kg load achieve bar speeds greater than 1.2 m•s-1, and "untrained" subjects achieve speeds less. Keywords: 1RM, Evaluation of the strength, functional profile, manifestations of strength.